Silence is a sense - AlAmmar, Layla (Chapel Hill, North Carolina : Algonquin Books of Chapel Hill, 2021)
"A woman sits in her apartment in an unnamed English city, absorbed in watching the dramas of her neighbors through their windows. Traumatized into muteness after a long, devastating trip from war-torn Syria to the UK, she believes that she wants to sink deeper into isolation, moving between memories of her absent boyfriend and family and her homeland, dreams, and reality. At the same time, she begins writing for a magazine under the pseudonym "the Voiceless," trying to explain the refugee experience without sensationalizing it-or revealing anything about herself. Gradually, as the boundaries of her world expand, she has to make a choice: Will she remain a voiceless observer, or become an active participant in her own life and in a community that, despite her best efforts, is quickly becoming her own?"--
General public
Keywords: Refugees -- Syria -- Fiction